Review of biopharmaceuticals and nutraceuticals from rice grain exploiting the endosperm, germ and bran for high-value innovation rice by-products - San Juan, Amor A. (2018)
Applying biotechnology innovation in rice is shown to produce promising biopharmaceuticals. The focus of this review is to critically examine the rice-derived biopharmaceuticals in contrast with rice-based therapeutics, its current progress, and future prospects. The article highlights the function-based analogy of an automobile car with the rice grain, aiming to understand the complexity of rice-based innovation encompassing biopharmaceutical and therapeutics. The combined endosperm, germ, and bran of rice consist of several bioactive compounds that result to a synergistic mechanism effect responsible for its health benefits. This article review shall hopefully encourage further relevant studies on rice product innovation as an added highend value to the rice industry. The perspective ends with a discussion on the challenges and opportunities for biopharmaceuticals and nutraceuticals.